Analisis Nilai-Nilai Pendidikan Karakter Pada Tari Ratoeh Jaroe di Pembelajaran Ekstrakurikuler SMA Negeri 3 Banda Aceh - Yeni Zuryaningsih; Febri Yanti (Misterius: Publikasi Ilmu Seni dan Desain Komunikasi Visual, 2024)
This research is entitled "Analysis of Character Education Values ​​in the Ratoeh Jaroe Dance in Extracurricular Learning at SMA Negeri 3 Banda Aceh". This research raises the issue of the value of character education in the Ratoeh Jaroe Dance in extracurricular activities. This research aims to analyze and describe the value of Ratoeh Jaroe Dance character education in extracurricular activities. The type of research used in this research is descriptive with a qualitative approach. The results of the research show that there is value in character education found in various movements, verse, floor patterns, fashion and make-up. The value of religious education is found in the various movements (saleum, aamiin and sep-sep), while in the verse namely (saleum, aamiin, lamburak, hasan summa husein, aroh pulo pineung and sep-sep), the dress code is in accordance with Islamic law. The educational value of nationalism is found in the various movements of the jakku timang, while in the verse namely the jak hai tajak and in traditional clothing. The value of independent education is only found in the verse of Hasan Summa Husein. The value of mutual cooperation education is found in the various movements (jak hai tajak, kasep kapot, uleue-uleue beu mate, lamburak, peulot manok, aroh pulo pineung, and uroe), and in the verse namely uleue-uleue beu mate and uroe. The value of integrity education is contained in the verse (jakku timang, kasep kapot, and peulot manok), and is found in a dancer namely Syeh.